Faktor-Faktor Yang Mempengaruhi Mahasiswa Akuntansi Dalam Memilih Karir Sebagai Akuntan Publik Pada Mahasiswa Akuntansi Perguruan Tinggi di Mojokerto - Tatas Ridho Nugroho; Hari Setiono; Nurul Insanin (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2020)
The purpose of this study was to determine the factors that influence career selection as a public accountant. Factors that influence the career choice of variables masured by financial reward, professional recognition, work environment, intrinsic value of work, and gender equality. This research uses a quantitative approach with the use of a questionnaire as a data collection tool. The sampling as many as 74 respondents obtained from universities in Mojokerto (UNIM, STIE Al-Anwar). The data analysis undertaken in this study is a classic assumption test, multiple linier analysis, the determination coefficients F-test, and t-test. The results of this study indicate that the variables of financial rewards, professional recognition, and work environment have a significant influence on career selection as a public accountant. While the intrinsic value of work and gender equality doesn’t have a significant influence on career selection as a public accountant.